المسؤولية المدنية الناشئة عن استخدام تقنيات الذكاء الا صطناعي في التشريع الجز ائري - لعمارة طارق زياد -ميمون سفيان (جامعة المسيلة, 2024)
المسؤولية المدنية عن استخدام الذكاء االصطناعي هو موضوع جديد في الجزائر، نظرا لعدم وجود تشريعات تنظيمية، فإن سن قوانين واضحة تحدد المسؤولية عن األضرار الناتجة عن استخدام هذه التكنولوجيا أمر ضروري، عالوة على ذلك يجب أن يكون جميع أصحاب المصلحة، بما في ذلك األفراد والمؤسسات، على دراية بمخاطر الذكاء االصطناعي والتزاماتهم عند استخدامها، تهدف دراستنا لتبيان مدى اكتساب الذكاء االصطناعي للشخصية القانونية. الكلمات المفتاحية: المسؤولية المدنية، الذكاء االصطناعي، الشخصية القانونية. Abstractt The civil liability for the use of artificial intelligence is a new topic in Algeria. Due to the absence of regulatory legislation, clear laws are necessary to define responsibility for damages resulting from the use of this technology Additionally, all stakeholders, including individuals and institutions, must be aware of the risks associated with artificial intelligence and their obligations when using it Our study aims to demonstrate the extent to which legal entities acquire responsibility for artificial intelligence. Keywords Civil responsibility, Artificial intelligence (AI), Legal personality
Keywords: : المسؤولية المدنية، الذكاء االصطناعي، الشخصية القانونية.